Filipino kitchen proxemics of the kitchen space in selected home of urban low income families - Tejada, Michelle Arevalo; Mayo, Adelaida Villaraza (2006.)
This study dealt with the Filipino concept of kitchen space among low-income families in an urban community. It focused mainly on the analysis and understanding of the design and utilization of the space using the theory of proxemics (Hall 1969). Factors such as socio-cultural values, customs and traditions, the socioeconomic status in terms of occupation and income were related to the design and space utilization. The respondents were selected low-income families living in the urban community of Towerville, a relocation site in Sto. Cristo, San Jose Del Monte, Bulacan. Most of them were previous residents of informal settlements that were demolished in the areas of Navotas, Pasay, and Manila. They were given lands in Towerville where they built their own houses on. They were all nuclear families of households with the husbands as the head of the family. They were chosen on the basis of ease or convenience with the help of a resident contact person in the community. Ten families were picked from the population. The derived data were gathered through in-depth interviews and observations with the aid of questionnaire-interviews and observation and interview guides. Photos were also taken for visual presentation in the discussion and analysis of data. Floor plans and layouts with corresponding dimensions were taken and presented to reinforce data. The kitchen as a fixed-feature space was defined in terms of the location and layout being proximity with the dining area and the toilet and bath room. Space allotted for the basic and specific functions of the kitchen such as preparing, cooking, washing, and storage areas were also analyzed. Findings showed that the use of the kitchen space among the respondent families also reflected the socio-cultural values and traditions of Filipino low-income families translated in the design. There were common food practices observed among them such as eating meals together at the dining table, saying prayers before and/or after meals and viewing the television or not while eating. Seating arrangements during meals following a hierarchy of space were also noted. Results showed that socio-economic factors, such as the family's standard or status of living, affect the treatment of space in terms of space allocation, choice of materials and finishes, color preferences, furniture, accessories and furnishings.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Kitchens -- Philippines -- Design and construction